Resiliensi dan Kondisi Psikologis Masyarakat di Masa Pandemi COVID-19 - Elok Faradisa; Ninuk Dian Kurniawati; Erna Dwi Wahyuni (Journal of Telenursing (JOTING), 2023)
This study aims to identify the factors that influence the formation of community resilience during the COVID-19 pandemic. The method used is a systematic review by identifying articles from four data based ScienceDirect, Scopus, Ebsco, and PubMed in 2020-2022. Articles were selected with PRISMA based on predetermined inclusion and exclusion criteria, using the keywords psychology, resilience, society, and COVID-19. The results showed that there were 4973 articles consisting of 802 ScienceDirect articles, 1179 Scopus articles, 1856 Ebsco articles, and 1136 PubMed articles. Based on the analysis, 16 full-text articles met the inclusion criteria for review. The study's results classify factors that affect community resilience during the COVID-19 pandemic into internal and external factors. Good stability in individuals can minimize the psychological impact and increase the positive effects in everyday life. In conclusion, the resilience formed by internal and external factors makes people able to survive the crisis of the COVID-19 pandemic, adapt, overcome psychological problems, and remain active in creative activities.